Analgesic effects of bulleyaconitine A: new advances in research from ion channel targets to clinical translation - Yin, Zili; Song, Xinlian; Zhu, Changcheng; Hou, Anguo; Chen, Rong (Frontiers in Pharmacology, 2026)
Chronic pain represents a significant global health concern, posing a severe threat to human wellbeing and affecting up to 20% of the adult population. Bulleyaconitine A (BLA), a diterpenoid alkaloid derived from plants of the Aconitum genus with in the Ranunculaceae family, demonstrates remarkable analgesic properties with a low potential for addiction, thus broad clinical application prospects compared to opioids. Extensive research has elucidated multiple pharmacological mechanisms underlying the analgesic effects of BLA, including state-dependent blockade of voltage-gated sodium channels, activation of the κ-opioid receptor pathway in spinal microglia, and anti-inflammatory immunomodulatory effects through inhibition of the NF-κB pathway. These mechanisms have been validated in various pain models, including neuropathic pain, cancer pain, rheumatoid arthritis pain, and visceral pain. However, BLA still faces pharmacokinetic challenges in clinical translation, including a narrow therapeutic window, low bioavailability, and potential neurotoxicity. In recent years, the development of novel drug delivery systems, structural modifications targeting the C-8 and C-14 sites to separate toxicity from efficacy, and advances in artificial intelligence-assisted drug design have provided effective solutions to overcome these limitations. Emerging research suggests that BLA has potential new indications in areas such as visceral hypersensitivity, irritable bowel syndrome, and pain-related anxiety disorders. This article provides a comprehensive review of the ion channel targets, central and peripheral mechanisms of action, pharmacokinetic characteristics, innovative drug delivery strategies, structural optimization pathways, and current clinical application of BLA. It aims to offer valuable references for the further development and rational clinical application of BLA as a non-opioid analgesic with multi-target therapeutic potential.